What do international tourists seek for when playing in the casinos? A Bucharest gambling market study - Lorin Dragan; Dana Hirgau (CES Working Papers, 2021)
The current study focuses on the gambling market, an area often considered part of the hospitality industry. We studied the casino market in Bucharest, Romania, aiming at profiling its customers. Initially, the proportion of foreigners among the players was analyzed. Furthermore, we determined the critical success and failure factors for those players by pursuing a content analysis approach. We found that locals constitute the majority of players, although in 2 out of 5 casinos studied, the foreigners were majoritarly. There were also important differences across cultures in terms of desired experience in terms of gambling.
Keywords: 330; gambling; casinos; hospitality